Formation, structure and promoting crystallization capacity of stereocomplex crystallite network in the poly(lactide) blends based on linear PLLA and PDLA with different structures. (1st June 2016) - Jing, Zhanxin; Shi, Xuetao; Zhang, Guangcheng; Li, Jiang; Li, Jianwei; Zhou, Lisheng; Zhang, Hongming
Abstract: A series of asymmetric PLLA/PDLA blends based on linear PLLA and PDLA (linear PDLA and star-shaped PDLA) were prepared by solution blending, and stereocomplex crystallites (sc-crystallites) were formed between PLLA and various PDLA due to strong hydrogen bonding. Rheological results indicated that the melt strength of PLLA was improved due to the network structure of sc-crystallites in the PLLA melt. The effect of PDLA on rheological behavior of the melt decreased in the following order: 6PDLA > L-PDLA > 3PDLA > 4PDLA. Dissolution experiment revealed that the formed network structure could be formed by interparticle polymer chains or branched points. Nonisothermal and isothermal crystallization showed that the promoting crystallization of sc-crystallites for PLLA was closely related to thermal treatment temperature, crystallization temperature and the structure of PDLA, and the PDLA structure could change the pattern of crystal growth during isothermal crystallization. Nucleation efficiency of sc-crystallites during non-isothermal crystallization decreased with increasing of arm numbers of PDLA. POM results also demonstrated that the nucleation and spherulite growth during isothermal crystallization were affected by the PDLA structure. This study has systemically investigated the effects of the PDLA structure on rheology and crystallization capacity of asymmetric PLLA/PDLA blends, which would provide potential approaches to control the microstructure and physical performances of PLLA/PDLA blends. Graphical abstract: Highlights: Preparation of asymmetric PLLA/PDLA blends based on linear PLLA and PDLA with different structures by solution blending. The improvement of rheological properties of PLLA/PDLA blends due to sc-crystallites and the formed network structure. Prediction of the structure of formed stereocomplex network. Investigation on the effects of sc-crystallites on crystallization behavior of the PLLA matrix.